1980
DOI: 10.4315/0362-028x-43.12.939
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt: Technology and Biochemistry

Abstract: This review considers the physical and chemical changes which occur during yogurt manufacture as a result of processing and microbial fermentation. Changes produced during processes, such as heat treatment and physical manipulations, are reviewed. Microbial fermentation is discussed in terms of the characteristics of the yogurt organisms, Lactobacillus bulgaricus and Streptococcus thermophilus, and the biochemical reactions involved in carbohydrate metabolism, flavor production, proteolysis and lipolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
264
1
27

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(302 citation statements)
references
References 0 publications
10
264
1
27
Order By: Relevance
“…Several methods are used to increase the shelf life of the product such as different packaging [15] , addition of antibiotics [16][17][18] , addition of gas [19] , application of preservatives, heat treatment after incubation [18] and carbonation process [20] .…”
Section: -10 D At <10°cmentioning
confidence: 99%
“…Several methods are used to increase the shelf life of the product such as different packaging [15] , addition of antibiotics [16][17][18] , addition of gas [19] , application of preservatives, heat treatment after incubation [18] and carbonation process [20] .…”
Section: -10 D At <10°cmentioning
confidence: 99%
“…bulgaricus strains were shown to be stably maintained in all combinations (10 8 e10 9 cfu/mL for each species at the end of yoghurt fermentation), and the acetaldehyde, ethanol, acetone, diacetyl and MEK contents of the yogurts were reported to be between 13.44 and 25.44 mg/L, 1.49e7.02 mg/L, 0.28e0.54 mg/L, 0.43e1.79 mg/L, and 0.04e0.11 mg/L, respectively. Acetaldehyde is considered to be the most important compound for the typical yogurt flavor (Gardini, Lanciotti, Guerzoni, & Torriani, 1999), and generally found between 17 and 41 mg/L in yoghurts (Abrahamsen, Svensen, & Tufto, 1978;Tamime & Deeth, 1980). Çelik (2007) indicated that 11 among 20 different yogurt combinations showed acetaldehyde production over 20 mg/L and the combination cTY63-2/b22 had the highest acetaldehyde content (25.444 mg/L).…”
Section: Technological Performances Of the Isolatesmentioning
confidence: 99%
“…Assessing the innocuous nature of S. thermophilus as a food microorganism is of major importance since this bacterium is widely used for the manufacture of dairy products [1][2][3] (annual market value of B$40 billion) 3 . In consequence, over 10 21 live cells are ingested annually by the human population.…”
mentioning
confidence: 99%